The External Conflict Faced by The Main Character in Five Feet Apart Movie - Diansari Artawan, Ni Made Prana; Shanti Sari Dewi, Anak Agung Sagung; Weddha Savitri, Putu (Udayana Journal of Social Sciences and Humanities; Vol 4 No 1 (2020): UJoSSH, February 2020, 2020)
The title of this study is The External Conflict Faced by The Main Character in Five Feet Apart Movie. This study focused on the external conflict faced by Stella Grant, the main character. The data of this study were taken from the Five Feet Apart movie and its script through documentation method and note-taking technique. The data is analyzed through qualitative research according to the theory of literature proposed by Kenney (1966) and Bernhardt (1953). Based on the analysis, it found that the main character faced man versus man and man versus nature external conflict. Man versus man conflict happens mostly in the movie. Meanwhile, for the psychological aspects that trigger the conflict, it is found only three from five classes of human motives that appear in this movie. Those motives are wanting, emotions, as well as feelings and attitudes.